Bacterial antimicrobial metal ion resistance. Issue 5 (May 2015) - Hobman, Jon L.; Crossman, Lisa C.
Abstract : N/A: Metals such as mercury, arsenic, copper and silver have been used in various forms as antimicrobials for thousands of years with until recently, little understanding of their mode of action. The discovery of antibiotics and new organic antimicrobial compounds during the twentieth century saw a general decline in the clinical use of antimicrobial metal compounds, with the exception of the rediscovery of the use of silver for burns treatments and niche uses for other metal compounds. Antibiotics and new antimicrobials were regarded as being safer for the patient and more effective than the metal‐based compounds they supplanted. Bacterial metal ion resistances were first discovered in the second half of the twentieth century. The detailed mechanisms of resistance have now been characterized in a wide range of bacteria. As the use of antimicrobial metals is limited, it is legitimate to ask: are antimicrobial metal resistances in pathogenic and commensal bacteria important now? This review details the new, rediscovered and 'never went away' uses of antimicrobial metals; examines the prevalence and linkage of antimicrobial metal resistance genes to other antimicrobial resistance genes; and examines the evidence for horizontal transfer of these genes between bacteria. Finally, we discuss the possible implications of the widespread dissemination of these resistances on re‐emergent uses of antimicrobial metals and how this could impact upon the antibiotic resistance problem.